2020
DOI: 10.24106/kefdergi.3696
|View full text |Cite
|
Sign up to set email alerts
|

Ergenlerde Saldırganlık: Duygu Düzenleme ve Duygusal Başa Çıkmanın Rolü

Abstract: Araştırmada ergenlerin saldırganlık (fiziksel saldırganlık, sözel saldırganlık, öfke, düşmanlık, dolaylı saldırganlık) düzeylerini duygu düzenleme ve duygusal başa çıkma becerilerinin ne düzeyde yordadığını belirlemek amaçlanmıştır. Araştırma 277'si (%58.3) kız ve 198'i (%41.7) erkek toplam 475 lise öğrencisi üzerinde gerçekleştirilmiştir. Araştırmada Saldırganlık Ölçeği, Ergenler İçin Duygu Düzenleme Ölçeği ve Duygusal Başa Çıkma Ölçeği kullanılmıştır. Veriler Pearson Momentler Çarpımı Korelasyon Katsayısı ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Öpöz (2017) concluded that as adolescents' emotion regulation difficulties increase, their anger control decreases significantly, while their trait anger levels increase significantly. Cenkseven Önder and Canoğulları (2020) concluded in their study that external dysfunctional emotion regulation significantly predicted anger. Similarly, Karababa (2020) found a positive and significant correlation between trait anger and external dysfunctional emotion regulation variables in his study examining the correlation between trait anger, emotion regulation strategies, and loneliness.…”
Section: Discussionmentioning
confidence: 98%
“…Öpöz (2017) concluded that as adolescents' emotion regulation difficulties increase, their anger control decreases significantly, while their trait anger levels increase significantly. Cenkseven Önder and Canoğulları (2020) concluded in their study that external dysfunctional emotion regulation significantly predicted anger. Similarly, Karababa (2020) found a positive and significant correlation between trait anger and external dysfunctional emotion regulation variables in his study examining the correlation between trait anger, emotion regulation strategies, and loneliness.…”
Section: Discussionmentioning
confidence: 98%